EDUKASI PEMBUKUAN UMKM RM SATE BEBEK H. SYAFE’I CIBEBER DENGAN APLIKASI BERBASIS DIGITAL - Ahmad Mukhlis; Mochamad Fahru Komarudin; Aan Wahyu Purnomo; Thessa Amalia; Rendi Halomoan (Indonesian Collaboration Journal of Community Services, 2022)
. Syafe'I Restaurant is a pioneer in the menu of satay and duck soup which are typical foods from Cibeber, Cilegon Banten, which was founded in 1977 until now in their daily lives they still use manual and traditional bookkeeping. KKM-PkM collaboration of students and lecturers at Bina Bangsa University tries to educate digital bookkeeping based on the BukuKas application to further increase the effectiveness and ease of producing financial reports so that strategic decisions can be made to win competition in the millennial era.